2020
DOI: 10.1109/access.2020.2966881
|View full text |Cite
|
Sign up to set email alerts
|

Review of Pavement Defect Detection Methods

Abstract: Road pavement cracks detection has been a hot research topic for quite a long time due to the practical importance of crack detection for road maintenance and traffic safety. Many methods have been proposed to solve this problem. This paper reviews the three major types of methods used in road cracks detection: image processing, machine learning and 3D imaging based methods. Image processing algorithms mainly include threshold segmentation, edge detection and region growing methods, which are used to process i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(96 citation statements)
references
References 88 publications
(87 reference statements)
1
92
0
3
Order By: Relevance
“…As can be seen from the figure, we notice that the block size has a huge impact on recognition accuracy. All cases the recognition rate increase except for Extended Yale B when [b 1 ,b 2 ]< [7,7], achieving the best performance when [b 1 ,b 2 ]= [7,7]. Also, the result suggests LMDAPNet with smaller block size on the occlusion test set of AR dataset achieves better results.…”
Section: ) Impact Of the Number Block Sizementioning
confidence: 88%
See 2 more Smart Citations
“…As can be seen from the figure, we notice that the block size has a huge impact on recognition accuracy. All cases the recognition rate increase except for Extended Yale B when [b 1 ,b 2 ]< [7,7], achieving the best performance when [b 1 ,b 2 ]= [7,7]. Also, the result suggests LMDAPNet with smaller block size on the occlusion test set of AR dataset achieves better results.…”
Section: ) Impact Of the Number Block Sizementioning
confidence: 88%
“…4 and Fig. 5, we briefly summarize the appropriate setting of the parameters for our LMDAPNet as follows: [b 1 ,b 2 ]= [7,7], while should be adapted according to the image size, and our experiences also show that it performs reasonably well when α = 0.4 in most cases.…”
Section: ) Impact Of the Block Overlap Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…For this experimental comparison, 9,000 images were taken with a smart phone and 15,000 objects were marked. The comparison showed that MobileNet utilizes 30.6 ms but did not work properly in detecting long and curved shapes such as cracks because this object detection algorithm is suitable for recognizing objects such as vehicles or people [21].…”
Section: B Road-damage Detection Using Artificial Intelligencementioning
confidence: 99%
“…The authors in [1] reviewed DL network application publications on pavement crack detection since its first appearance in 2016. The importance of the matter can be seen from a recent review paper on pavement defect detection methods [4]. The number of reviewed methods/publications exceeds 100, and half of them are not older than five years.…”
Section: Introductionmentioning
confidence: 99%